2017
DOI: 10.22456/1679-9216.80488
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cooling Time and Diluents on the Freezability of Prochilodus brevis semen

Abstract: Background: Prochilodus brevis is a rheophilic fish of economic and ecological importance. However, anthropic action has made its population vulnerable. Thus, the development of reproductive biotechnologies, such as seminal conservation, is necessary to subsidize their fish farming. However, seminal collections are often performed in places with few laboratory resources, demanding studies to determine the maximum time for which sperm can be cooled, as well as its process until frozen. Thus, the present study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…The mean volume of semen obtained from the breeders used in the present study was higher than that reported by Nunes et al (2016) and Nascimento et al (2017), who presented a mean of 0.56 ± 0.24 and 0.54 ± 0.23 ml, respectively. A similar result was observed with sperm concentration, with the values obtained in the present study being higher than those reported by these authors.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The mean volume of semen obtained from the breeders used in the present study was higher than that reported by Nunes et al (2016) and Nascimento et al (2017), who presented a mean of 0.56 ± 0.24 and 0.54 ± 0.23 ml, respectively. A similar result was observed with sperm concentration, with the values obtained in the present study being higher than those reported by these authors.…”
Section: Discussioncontrasting
confidence: 82%
“…These data can also be used to work with cryopreserved semen. As cryopreserved semen of this species is generally diluted 1:9 (semen:diluent, Nunes et al, 2016;Nascimento et al, 2017), it is recommended to use 0.25 ml straws of cryopreserved semen (motile > 80%) to 0.76 g ova or 37.4 straws per female (spawn weight ∼28.40 g). In the case of cryopreserved semen with motility close to 50%, it is recommended to use twice the dose mentioned above.…”
mentioning
confidence: 99%
“…They belong to the Laboratory of Biotechnology of Fish Reproduction (LBRP), located at the State University of Ceará, Fortaleza, Ceará, Brazil. Hormonal induction to reproduction and management to obtain milt from P. brevis were carried out according to standard laboratory procedures (Nunes et al, 2016;Nascimento et al, 2017). The doses of carp pituitary extract administered were 0.4 and 4.0 mg kg -1 of body weight.…”
Section: Experiments 2: Effect Of Freezing Medium Supplementation With Gags On Seminal Cryopreservation Of P Brevis Experimental Animals mentioning
confidence: 99%
“…Studies related to the seminal cryopreservation of P. brevis have already been carried out, in which were tested different dilution rates (Lopes et al, 2014), forms of milt storage (Nascimento et al, 2017), forms of dilution (Lopes et al, 2014;Nunes et al, 2016) and freezing methods (Pinheiro et al, 2016). There is a good interaction of P. brevis sperm with the freezing medium composed of 5% glucose and 10% dimethyl sulfoxide (DMSO), both for sperm kinetics parameters (Nunes et al, 2016) and the fertilization capacity (Nunes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation